Sarcoid uveitis in a patient with multiple neurological lesions: a case report and review of the literature - Tomoko Ohno; Mami Ishihara; Etsuko Shibuya; Nobuhisa Mizuki (Journal of Medical Case Reports, 2018)
Abstract Background Neurosarcoidosis is a rare complication, and cranial neuropathy is the most frequent manifestation of this disease. However, few cohesive reports have discussed multiple cranial neuropathies in Japanese patients with sarcoidosis. The present report discusses the case of a patient with sarcoid uveitis and multiple neurological findings. We further review relevant literature regarding Japanese patients with multiple cranial nerve palsies published within the past 34 years (from January 1982 to December 2016). Case presentation We report findings associated with the case of a 56-year-old Japanese woman with granulomatous pan-uveitis who was later diagnosed as having sarcoidosis by skin and transbronchial lung biopsies. She presented right-sided Bell’s palsy and was treated with orally administered prednisolone. However, while prednisolone was tapered, she developed facial (VII) and vagus (X) nerve palsies, followed by brain parenchyma lesions, which were not associated with any additional neurological symptoms. Furthermore, she exhibited increased intraocular pressure in her right eye, and she underwent trabeculectomy. Our review of the literature revealed that 64 Japanese patients with sarcoidosis experienced multiple cranial nerve palsies between 1982 and 2016. The most commonly affected cranial nerves were the facial (VII) (73.4%) and glossopharyngeal/vagus (IX/X) nerves (48.4%). Palsies of two distinct cranial nerves were found in 40.6% of the patients, followed by palsies of three (23.4%) and four (18.8%) nerves. Almost all patients (98.3%) received systemic steroid therapy, and total or partial remission was achieved in almost all patients (96.5%). Conclusions According to the literature, patients with multiple cranial nerve palsies associated with sarcoidosis respond well to orally administered steroid therapy. However, our findings suggest that careful follow-up is necessary for patients with neurosarcoidosis due to potential aggravation of neuropathy.